Microbial activity, methane production, and carbon storage in Early Holocene North Sea peats - Lippmann, Tanya J. R.; 't Zandt, Michiel H. in; Van der Putten, Nathalie N. L.; Busschers, Freek S.; Hijma, Marc P.; van der Velden, Pieter; de Groot, Tim; van Aalderen, Zicarlo; Meisel, Ove H.; Slomp, Caroline P.; Niemann, Helge; Jetten, Mike S. M.; et al. (Biogeosciences, 2021)
Northern latitude peatlands act as important carbon sources and sinks, but little is known about the greenhouse gas (GHG) budgets of peatlands that were submerged beneath the North Sea during the last glacial–interglacial transition. We found that whilst peat formation was diachronous, commencing between 13 680 and 8360 calibrated years before the present, stratigraphic layering and local vegetation succession were consistent across a large study area. Large carbon stores were measured. In situ methane (CH 4 ) concentrations of sediment pore waters were widespread but low at most sites, with the exception of two locations. Incubation experiments in the laboratory revealed molecular signatures of methanogenic archaea, with strong increases in rates of activity upon methylated substrate amendment. Remarkably, methanotrophic activity and the respective diagnostic molecular signatures could not be detected. Heterotrophic Bathyarchaeota dominated the archaeal communities, and bacterial populations were dominated by candidate phylum JS1 bacteria. In the absence of active methanogenic microorganisms, we conclude that these sediment harbour low concentrations of widespread millennia-old CH 4 . The presence of large widespread stores of carbon and in situ methanogenic microorganisms, in the absence of methanotrophic microorganisms, holds the potential for microbial CH 4 production if catalysed by a change in environmental conditions.